The timeshare industry of Africa: a study in tourism geography - Pandy Wayde R.; Rogerson Christian M. (Bulletin of Geography. Socio-Economic Series, 2013)
Within the broad spectrum of tourism accommodation the timeshare industry is a distinctive segment which has attracted only limited research work. This paper represents a contribution to tourism geography as it investigates the location of timeshare resorts in Africa and comparative position of African destinations in the global timeshare economy. The analysis shows the timeshare resort industry in South Africa is the most significant on the continent and is distinctive in its reliance upon domestic rather than international tourists. In terms of the distribution of resorts the key locational consideration in Africa parallels that found in other parts of the world, namely the positioning of resorts in areas of high natural amenity. In the African context this has meant clustering resorts in coastal beach areas and attractive mountain locations, as well as in the areas which afford opportunities for timeshare consumers to experience the African bush. Finally, of note in South Africa is the growth of large timeshare property developments at casino resorts, a development which parallels the experience of certain timeshare developments in the USA.